The effect of nozzle type on air entrainment by plunging water jets - Bagatur, T; Baylar, A; Sekerdag, N (Canadian Assoc Water Quality, 2002)
In this study, for the plunging water jet aeration system using various inclined nozzle types, bubble penetration depth, air entrainment rate, water jet expansion, effect of water jet circumference at impact point, oxygen transfer coefficient and oxygen transfer efficiency which changed depending on the water jet velocity, were researched in an air-water system. Numerous studies were conducted with circular nozzles. The present study describes new experiments performed with different nozzle types. Three types of nozzles were examined, i.e., those with circular, ellipse and rectangle duct with rounded ends. Experimental results showed that water jets produced with ellipse and rectangle duct with rounded ends nozzles have very different flow characteristics, entrainment patterns on free water jet surface, and submerged water jet region within the receiving tank. Higher air entrainment rate and oxygen transfer efficiency was observed in the rectangle duct with rounded ends nozzle due to water jet expansion. Bubble penetration depth, however, is lower for the rectangle duct with rounded ends nozzle than for the other nozzles. The ellipse nozzle provided the highest bubble penetration depth. These results showed that it is appropriate to use ellipse nozzle in aeration of deep pool and rectangle duct with rounded ends nozzle in the applications where high bubble concentration is desirable.
Keywords: plunging water jet; nozzle; air entrainment; aeration; dissolved oxygen